(untitled) (Eurasian Journal of Ecology, 2025)
Lake Taldykol is a water body that experiences significant anthropogenic impact, which is reflected in its hydrochemical and hydrobiological state. In this paper, a comprehensive analysis of water quality is carried out, including a study of the chemical composition, saprobity and structure of plankton communities. The aim of this work was to assess the species composition, abundance and biomass of phytoplankton and zooplankton of Lake Taldykol, as well as to determine possible changes in the structure of these communities under the influence of hydrological and environmental factors, in particular, under conditions of fluctuating water levels. The scientific significance of the work lies in the comprehensive study of anthropogenic impact on the reservoir and determination of its ability to self-purify. The practical significance lies in the possibility of using the obtained data to develop measures to protect and restore the lake ecosystem. The study revealed that the maximum permissible concentrations were exceeded for a number of pollutants, such as COD, suspended solids, phosphates, nitrites and iron, which indicates a high anthropogenic load. The dynamics of the number and biomass of phytoplankton and zooplankton indicate seasonal changes in the trophic level of the reservoir. Saprobic indices showed that the lake belongs to the β-mesosaprobic zone, but in spring and autumn there is a deterioration in water quality. Key words: phytoplankton, zooplankton, hydrochemistry, hydrobiocenosis.